Effect of enhancing urea-humic acid mixture with refined acid sulphate soil - Mohd Yusuff, Mohd Taufik; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2009)
Problem statement: Acid Sulphate Soil (ASS) is a problem soil partly because of its high acidity. This low pH could be exploited to reduce ammonia loss from urea by reducing soil microsite pH. The use Humic Acid (HA) to control ammonia loss from urea has been reported but the cost of this material is high. This laboratory study compared the effect of enhancing urea-humic acid mixtures with acid sulphate soil on NH3 loss, pH, exchangeable ammonium and available nitrate contents. Approach: Humic acid, acid sulfate soil and soil used in the incubation study were analyzed for selected soil physical-chemical properties using standard procedures. Urea-HA-ASS mixtures were prepared and ammonia volatilization of the mixtures was evaluated by the closed-dynamic air flow system. The treatments were evaluated in a randomized complete block design with 3 replications. Standard procedures were used to determine ammonia loss, soil pH, exchangeable ammonium and available nitrate at 22 days of incubation. Data obtained were analyzed using analysis of variance and Duncan's test using Statistical Analysis System (SAS) version 9.2. Results: Urea amended with 0.75 g ASS significantly reduced ammonia volatilization. Although the use of appropriate amount of acid sulphate soil to control ammonia loss is possible, excessive use of this material is not recommended because of Fe in it. Conclusion: Urea amended with 0.75 g ASS reduced ammonia.